Globalization and Local Determinants of HORECA Customers Market Behavior in the Wholesale Food Market - Yuriy Hubeni; Oksana Krupa; Volodymyr Krupa; Nataliia Raiter (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article is devoted to the research of local determinants of HoReCa sphere subject economic behavior in the wholesale markets of agricultural production under hospitality sphere globalization in Ukraine. The authors generalized the key provisions of consumer market behavior theories and its formation factors in HoReCa sphere. The peculiarities of agricultural wholesale market functioning are defined and the competitive surrounding of wholesale food market in western region of Ukraine is characterized. Main principles of business organization in HoReCa sphere are studied; the impact of globalization and foreign economic activity vectors on this sphere internationalization is outlined. The results of research project made by the authors are given, which was aimed at examining motives and peculiarities of HoReCa customers market behavior when wholesale purchasing agricultural production for their own business. The research was conducted on the basis of “Shuvar” market of agricultural production Ltd. - the largest in Western Ukraine wholesale agricultural market. It consists of several specialized food halls, including HoReCa centre. The structure of HoReCa establishments, that are “Shuvar” wholesale market clients, is analyzed. The factors influencing their managers’ decisions, concerning purchase assortment, its frequency, the most convenient time of goods delivery, are investigated. The evaluation of significance degree of certain products purchase, including price, products homogeneity, their constant availability, exclusiveness, is received. HoReCa sphere subjects’ wishes were studied, concerning purchase information support in the wholesale market, for service quality improvement.